2008
DOI: 10.1007/s00421-008-0729-3
|View full text |Cite
|
Sign up to set email alerts
|

Loss of neuromuscular control related to motion in the acutely ACL-injured knee: an experimental study

Abstract: Ligamentomuscular and muscular stretch reflexes are known to contribute to knee joint stability. After anterior cruciate ligament (ACL) injury, a more intense and adjusted muscular response is required to maintain joint stability, but this neuromuscular control of the knee has not been clearly proved. The aim of the study is to record electromyography (EMG) signal and muscular fibre length variations in quadriceps and hamstrings of the knee with and without ACL, and to analyze and integrate the ligament strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 50 publications
0
10
0
1
Order By: Relevance
“…Based on animal models, it is known that transection of the ACL increases the risk for initiation of cartilage breakdown and leads to a degeneration of the structures surrounding the knee joint (Herzog et al, 1993;Brandt et al, 1991;Galois et al, 2004). Consistent with this, recent observations in humans give evidence that ACL deficiency is associated with knee joint instability (Stergiou et al, 2007), afferent sensory dysfunction (Roos et al, 2010;Bonsfills et al, 2008;Konttinen et al, 2006), knee extensor muscle weakness (Suter and Herzog, 2000;Roos et al, 2010) and increases the risk for knee joint pain and osteoarthritis (OA; Herzog et al, 2003;Suter and Herzog, 2000;Roos et al, 2010). Further, it is known that ACLd patients show lower knee joint moments during stance phase for a variety of gait tasks, such as walking (Lewek et al, 2002;Rudolph et al, 2001), running (Rudolph et al, 2001) and stair climbing (Rudolph and Snyder-Mackler, 2004).…”
Section: Introductionmentioning
confidence: 77%
“…Based on animal models, it is known that transection of the ACL increases the risk for initiation of cartilage breakdown and leads to a degeneration of the structures surrounding the knee joint (Herzog et al, 1993;Brandt et al, 1991;Galois et al, 2004). Consistent with this, recent observations in humans give evidence that ACL deficiency is associated with knee joint instability (Stergiou et al, 2007), afferent sensory dysfunction (Roos et al, 2010;Bonsfills et al, 2008;Konttinen et al, 2006), knee extensor muscle weakness (Suter and Herzog, 2000;Roos et al, 2010) and increases the risk for knee joint pain and osteoarthritis (OA; Herzog et al, 2003;Suter and Herzog, 2000;Roos et al, 2010). Further, it is known that ACLd patients show lower knee joint moments during stance phase for a variety of gait tasks, such as walking (Lewek et al, 2002;Rudolph et al, 2001), running (Rudolph et al, 2001) and stair climbing (Rudolph and Snyder-Mackler, 2004).…”
Section: Introductionmentioning
confidence: 77%
“…In this study, we suggested that ACL transection-induced proprioceptive deficits might partially explain our ladder results. Indeed, a previous cat study showed that proprioceptive information was strongly disturbed after ACL rupture (2). Authors found that the information which originated from secondary articular stabilizers to the sectioned ACL could not be enough to ensure a motor control adjustment for stabilizing the knee.…”
Section: Discussionmentioning
confidence: 98%
“…Given that ACL injury could disturb articular, cutaneous, and mainly muscle mechanosensitive (proprioceptive) information, it was suggested, both in animal and human studies, that these sensitive impairments might contribute to motor reflex alteration (2,4,12). Furthermore, previous studies indicated that the muscle metabosensitive (groups III and IV) afferent activity was also disturbed after medial collateral ligament (MCL) injury in rats, affecting motor reflex activity (16).…”
mentioning
confidence: 96%
“…Likewise, it is well known that ACL injuries are associated with poor neuromuscular control, which leads to diminution of the proprioceptive information as a function of changes to the efficiency of the mechanical receptors responsible for neuromuscular control, 27 disturbances of the somatosensory system 28 and decreased muscle activation and force. 29 According to Hewett et al, 30 coordinated coactivation of the hamstrings and quadriceps has an important role in decreasing the risk of primary injury.…”
Section: Discussionmentioning
confidence: 99%